TERRORIST FINANCING IN THE DIGITAL AGE: AN ANALYSIS OF CRYPTO CURRENCIES AND ONLINE CROWD FUNDING - Ogele, Eziho Promise (UI Scholars Hub, 2024)
This study examines the potential risks of emerging payment technologies and value transfer systems in facilitating terrorist activities. Through an analysis of publications, blogs, and websites associated with terrorist groups and their supporters, the research reveals a growing interest in leveraging cryptocurrencies like Bitcoin and online crowdfunding platform to support funding, planning, and implementation of terror attacks. While concrete evidence of large-scale cryptocurrency use by terrorist groups is limited, there are indications of links to several terror attacks globally. This study demonstrates the potential for cryptocurrencies to facilitate clandestine activities, utilizing a document published by ISIS that outlines instructions undetected. By analyzing this document, researchers highlighted the potential risks associated with the anonymous and decentralized nature of cryptocurrency transactions. The study adopted actor-network theory as its theoretical underpinning. The findings suggest that terrorist organizations are actively exploring new technologies to mitigate risks associated with traditional fund transfer methods, with some websites collecting donations in Bitcoin. The study recommends amongst others that the Law enforcement agencies must enhance their capabilities to track cryptocurrency transactions, which include training investigators in illicit finance investigations involving cryptocurrencies, recruiting experts in the field, and acquiring advanced IT systems despite the challenges.